Development of a displacement controlled boom service for an excavator with a digital displacement pump motor - Hutcheson, John (The University of Edinburgh, 2025)
This thesis documents the development of a displacement controlled boom system for an excavator using a Digital Displacement Pump Motor. A review of the literature indicated that displacement controlled open circuit hydraulic systems showed promise for reducing fuel consumption in mobile machines. By applying a Digital Displacement Pump Motor to an excavator boom, this thesis expands on this research and fills a gap in the literature. The round trip efficiency of a Digital Displacement Pump Motor when controlling the motion of a loaded cylinder was measured. A detailed efficiency analysis of the pump was conducted under varying system pressures, displacements, and shaft speeds. The range of efficiencies measured was between 63% and 87%. The study provides valuable insights into the system efficiency of a Digital Displacement Pump Motor controlling a hydraulic cylinder in open circuit displacement control. A valve arrangement and control software was developed for controlling an excavator boom in open circuit displacement control with a Digital Displacement Pump Motor. A key component of this work involved characterising various valve types and developing a custom valve block, known as an H-Bridge. This approach allowed the incorporation of multiple control modes into a single system, enabling more flexibility in terms of control options. Two innovative control strategies—discrete throttling and differential lowering—were introduced and investigated. Both strategies leveraged the pump's ability to rapidly change its flow output, demonstrating that these mode switches would be possible with simple switching valves instead of proportional valves. The system was tested on a JS160 excavator to assess single function performance and the impact on fuel savings during standardised testing. The lack of pump/motor on the excavator meant that motoring could not be directly tested however the tests quantified the recoverable energy during various drive cycles through use of a motoring simulator device. A simulation study gave insights into how the system efficiency could be further improved by increasing hose sizes and fitting less restrictive hose burst valves. Energy recovery efficiency from the boom was measured to be 31% during the JCMAS testing however the simulation showed that this could be increased to as much as 64% if these changes were made. Ultimately the research presents several contributions to the field of hydraulic excavator systems and the application of Digital Displacement Pump Motors, opening avenues for future research and refinement. The findings highlight the potential of Digital Displacement technology and open circuit displacement controlled systems to improve the efficiency and performance of hydraulic excavators, leading to reduced CO₂ emissions and a more sustainable future for construction machinery.
Keywords: efficiency; hydraulic system for excavators; Digital Displacement Pump Motor; energy recovery efficiency; H-Bridge; discrete throttling; differential lowering; performance; fuel savings